How low can you go? Charity reporting when donations signal income and generosity - Anat Bracha; Lise Vesterlund (Federal Reserve Bank of Boston, 2013)
Consistent with nonprofit fundraising practices, donation visibility has been shown to increase giving. While concern for status is used to explain this response, the authors argue that this explanation relies on the assumption that giving signals only income or generosity. When giving signals both attributes overall status need not increase in donations, and donation-visibility may be harmful when individuals prefer to be perceived as poor-and-generous rather than rich-and-stingy. Using an experiment the authors find that both income-status and generosity-status concerns affect behavior. Furthermore, donation-visibility fails to increase contributions as low-income individuals select low donation amounts that are unlikely to be attributed to high-income individuals.
Keywords: C91; D01; D80; H41; 330; charitable donations; lab experiments; status; crowding out